Integrating Artificial Intelligence in STEM Education: Enhancing 21st Century Skills in Zimbabwean Universities - Doris Chasokela (Scientia Publica Media, 2025)
In recent years, integrating Artificial Intelligence (AI) into STEM education has emerged as a critical focal point in Zimbabwean universities, aimed at enhancing essential 21st-century skills among students. As AI continues to exert transformative effects across various sectors, it becomes imperative for students to cultivate the competencies necessary to thrive in an increasingly AI-driven economy. This qualitative study investigates the nuances of AI integration within the STEM educational framework in Zimbabwe, emphasising the potential benefits, prevailing challenges, and strategic methodologies for successful implementation. To gather comprehensive insights, semi-structured interviews were conducted with 30 diverse participants, including students, lecturers, university administrators, and industry experts. Thematic analysis of the data collected unveiled three central themes: the urgent need for AI literacy and skill development, the significance of contextualised learning through industry partnerships, and the existing challenges related to infrastructure and resource limitations. Findings from this study underscore the necessity for a holistic approach toward AI integration in STEM education. It highlights the critical role of curriculum development that encompasses AI technologies, ongoing faculty training to keep lecturers abreast of evolving trends, and collaborative efforts with industry stakeholders to ensure relevant and up-to-date learning experiences. Furthermore, the recommendations derived from this research hold potential implications for educational policy and practice, not only within Zimbabwe but also for other developing nations grappling with similar challenges. By promoting an AI-enhanced educational framework, Zimbabwean universities can better prepare their students to meet the demands of the modern workforce and cultivate a generation equipped with the relevant skills needed for success in the complex landscape of the 21st century.